TARI RENTAK GUMANTAN: PERKEMBANGAN BENTUK DARI TARI GUMANTAN DI DESA PISANG BEREBUS KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Gustri Wella; Desfiarni Desfiarni; Afifah Asriati (SENDRATASIK UNP, 2013)
Abstract This article aims to describe the development of the Gumantan dance type in Pisang Berebus Village Gunung Toar Rengency, Kuantan Singingi District, Riau Province. Type of the research is qualitative with descriptive analysis method. The techniques of data collection are literature study, observation, interviews, photo shoot and recording. The technique of the data analysis is to classifying the data based on the conceptual framework.  The result showed that: the development of Gumantan dance influenced by citizen in that area. The purpose of the citizen in that area is to the make Gumantan dance still exist so that Lukman Edi created Rentak Gumantan dance. The developments of that dance can we see from the part of elements. Those elements are movements, space design, music dance, costumes, the dance dynamics and composition group.   Kata kunci: Perkembangan, Bentuk, dari, tari, Gumantan